Isolation and characterization of rat primary lung cells - Bundschuh, Daniela S.; Uhlig, Stefan; Leist, Marcel; Sauer, Achim; Wendel, Albrecht (My University, 1995)
Lung cell culture may be useful as anin vitro alternative to study the susceptibility of the lung to various toxic agents. Lungs from female Wistar rats were enzymatically digested by recirculating perfusion through the pulmonary artery with a sequence of solutions containing deoxyribonuclease, chymopapain, pronase, collagenase, and elastase. Lung tissue was microdissected and resuspended and the cells obtained were washed by centrifugation. By this isolation method, 2×108 cells per rat lung were obtained with an average viability of 97%. Lung cells cultured in medium containing antibiotics and serum maintained a viability of >70% for 5 d. Rat primary lung cells were exposed to various toxic agents and their viability was assessed by formazan production capacity after 18 h of incubation. Compared to rat and mouse hepatocyte cultures (EC50=5.8 mM), rat primary lung cells were much more susceptible to hydrogen peroxide (EC50=0.6 mM). All cell types were equally sensitive to the more potent toxicanttert-butylhydroperoxide (EC50=0.1 mM). Paraquat was more toxic to lung cells (EC50=0.03 mM) than to rat (EC50=2.8 mM) and mouse (EC50=0.2 mM) hepatocytes. In contrast, rat lung cells were less sensitive to sodium nitroprusside (EC50=2.6 mM) compared to rat (EC50=0.2 mM) and mouse (EC50=0.03 mM) hepatocytes. Nitrofurantoin and menadione (at EC50=0.04 mM and 0.006 mM, respectively) were more toxic to rat lung and liver cells than to murine hepatocytes (EC50=0.2 mM and 0.04 mM, respectively). Our findings demonstrate the applicability of this rat primary lung cell culture for studying the effects of lung toxicants.
Keywords: 570